Leksikografi Al-Qur'an Ke Arah Penyusunan Kamus Al-Qur'an - Hanafi, Muchlis Muhammad (SUHUF, 2009)
This writing is explaining the development of the lexicography of the Qur’an, starting from the history of its emergence, the works that have been written, both personally or institutionally and the method being used. One of the problems the Muslim scholars concern about is the words of the Qur’an. It is because not all of the Arabs at the time the Qur’an was revealed understood all the words the Qur’an used. The uniqueness and the richness of the Arabic language has made the language of the Qur’an cannot all be understood and even considered by some of the Arabs to be extremely strange. The language of the Qur’an is of two kinds; some are those that can be understood easily by the Arabs and some can only be understood by certain people of the Arabs. The second group of the words is commonly known in the Arabic lexicography as garīb Al-Qur’an (the strange words of the Qur’an).